Sustainable Universities, from Indifference to Joint Action – A Panel Data Analysis - Elena-Claudia Șerban; Anca-Maria Hristea; Ștefania-Cristina Curea; Raluca-Florentina Crețu (Amfiteatru Economic)
The implementation of the sustainable development concept within academic environments is one of the top priorities of the national and international academic management. The aim of the article was the analysis of the weights of the five Universitas Indonesia GreenMetric criteria used to assess the academic sustainability level, which determine the final ranking score. The initial observance period was ten years but since the individual criteria weights were not included in the 2010-2013 reports, the analysis period was reduced to six years. The sample encompassed universities from Europe. This choice was determined by the fact that the highest ranked universities in the rankings used for the research were European universities. The selection included 58 universities from 18 countries. The data was processed through the Eviews software using the Ordinary Least Square method, with corrections for the fixed effects panel data. The results of the research confirm that the strength of the connection between the five criteria for assessing sustainability at the university level and the total score of hierarchy of sustainable universities is very high. The purpose of this paper is finding conclusions concerning the probability, for some universities included in this ranking system, of gradually adjusting their sustainability level through the most susceptible indicators by the human factor.